Lipase production by immobilised Rhizopus arrhizus - Elibol, M; Özer, D (Elsevier Sci Ltd, 2000)
Immobilisation of Rhizopus arrhizus cells on a solid support (polyurethane foam) for lipase production has been explored. Lipase biosynthesis was repressed at a high glucose level. Maximum productivity was recorded at 1 g l(-1) glucose concentration. The inclusion of 0.5 g l(-1) corn oil (as an inducer) in the fermentation medium resulted in 2.5-fold higher lipase production compared to the control where no oil was added. Repeated-batch experiments revealed that immobilised R. arrhizus cells demonstrated reproducible behaviour, producing the same amount of enzyme over a 120 h period. The storage stability of the enzyme was investigated and enzyme activity reduction was 26% within 160 h. (C) 2000 Published by Elsevier Science Ltd. All rights reserved.
Keywords: lipase; immobilised Rhizopus arrhizus; lipolytic activity; inducer